Age-related characteristics of infective endocarditis: prospective data from the Euro-Endo registry. (25th November 2020) - Pazdernik, M; Selton-Suty, C; Lancellotti, P; Kong, W.K.F; Srdanovic, I; Yamada, H; Riezebos, R.K; De Martino, A; Pierard, L; Nunes, M; Haertel Miglioranza, M; Magne, J; et al.
Abstract: Introduction: The profile of infective endocarditis (IE) is continuously evolving over time, and this may probably be partly due to increasing age of the patients. Methods: All data were collected from the EURO-ENDO registry, which is a one-year prospective international multicentre observational survey on patients with definite or possible IE included between 2016 and 2018. Subjects were stratified into 3 groups according to their age at index hospitalization. Results: Among the 3113 patients included, 1670 patients (54%, Young group) were <65, 1068 (34%, Medium group) between 65 and 80 and 375 (12%, Old group) ≥80 years old. The most striking age-related differences were (old group vs others) (table 1) 1) the higher comorbidity burden and Charlson index; 2) the lower rate of embolic events on admission and under therapy; 3) the higher rate of Enterocci and digestive streptococci; 4) the lower rate of surgery during acute IE despite a theoretical indication; 5) the higher in-hospital and 1-year mortality. With regards to surgery, young and medium age were predictive of more frequent performance of surgery as compared to old age (Young: OR 4.33, 95% CI [3.09–6.06], Medium: 3.62, [2.57–5.10], p<0.001). In multivariable analysis, age per se was not predictive of in-hospital and 1yr FU mortality, but lack of surgical procedures when indicated (27% of the old group), was strongly predictive. Conclusion: This is the largest contemporary registry showing the strong influence of age on the demographic, clinical, therapeutic, and prognostic profile of IE. Non-performance of surgical procedures when indicated is frequent in old patients and is a strong predictor of mortality while age per se is not. Endocarditis Teams should take these results into account when considering surgery in elderly patients. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): EORP grant